Spectrophotometric Determination of Nitrogen dioxide in the Environment - Kashyap, Anupama; Chatterjee, S.; Kumar Kashyap, Anil; Gupta, V.K. (Asian Journal of Chemistry, 2010)
In the present investigation a simple, sensitive and selective spectrophotometeric method for the determination of nitrogen dioxide in air has been described. The air sample containing nitrogen dioxide is passed through the absorbing solution of acidified potassium iodide to liberate iodine. The liberated iodine bleaches the pinkish-red colour of rhodamine-B dye, which measured at 555 nm. The proposed regent has ca. 99 % collection efficiency and stoichiometric ratio of NO2:NO2– is 0.77 Beer's law obeyed over the concentration rage of 0.2-2.0 μg of nitrite/25 mL (0.008-0.08 ppm). The molar absorptivity and Sandell's sensitivity were found to be 5.25 × 105 dm3 mol-1 cm-1 and 0.000087 μg cm-2, respectively. The method has been applied for the determination of nitrogen dioxide in autoexhaust and cigarette smoke.